Report from the strawberry cultivar field trials in northern Norway, Sweden and Finland 2005 and 2006 - Samuelsen, Ragnar T.; Öberg, Elisabeth; Jokela, Kirsi; Heinonen, Alpo; Haugland, Espen (no, 2007)
v